Fabrication and piezoelectric properties of BaTiO3/BaTiO3-Bi(Mg1/2Ti1/2)O3-BiFeO3 composites. Issue 9 (15th June 2018) - Fujii, Ichiro; Ariizumi, Shin; Ueno, Shintaro; Moriyoshi, Chikako; Kuroiwa, Yoshihiro; Wada, Satoshi
Abstract: We fabricated xBaTiO3 (BT)/(1-x)[BaTiO3 -Bi(Mg1/2 Ti1/2 )O3 -BiFeO3 ] (BT-BMT-BF) + 0.1 wt%MnCO3 composites by spark plasma sintering and investigated the effect of BT content x, BT powder size, and BT-BMT-BF composition on piezoelectric properties. For xBT/(1-x)(0.3BT-0.1BMT-0.6BF) + 0.1 wt%MnCO3 (x = 0–0.75) composites with a 0.5-µm BT powder, the dielectric constant was increased with x, and the relative density was decreased at x = 0.67 and 0.75, creating optimum BT content of x = 0.50 with a piezoelectric constant d 33 of 107 pC/N. When a larger 1.5-µm BT powder was utilized for the composite with x = 0.50, the d 33 value increased to 150 pC/N due to the grain size effect of the BT grains. To compensate for a compositional change from the optimum 0.3BT-0.1BMT-0.6BF due to partial diffusion between the BT and 0.3BT-0.1BMT-0.6BF grains, a 0.5BT/0.5(0.275BT-0.1BMT-0.625BF) + 0.1 wt%MnCO3 composite with the 1.5-µm BT powder was fabricated. We obtained an increased d 33 value of 166 pC/N. These results provided a useful composite design to enhance the piezoelectric properties.